Masculinities in Forests Representations of Diversity - Colfer, Carol J. Pierce (The Earthscan Forest Library, 2021)
Masculinities in Forests: Representations of Diversity demonstrates the wide variability in ideas about, and practice of, masculinity in different forests, and how these relate to forest management. While forestry is widely considered a masculine domain, a significant portion of the literature on gender and development focuses on the role of women, not men. This book addresses this gap and also highlights how there are significant, demonstrable differences in masculinities from forest to forest. The book develops a simple conceptual framework for considering masculinities, one which both acknowledges the stability or enduring quality of masculinities, but also the significant masculinity-related options available to individual men within any given culture. The author draws on her own experiences, building on her long-term experience working globally in the conservation and development worlds, also observing masculinities among such professionals. The core of the book examines masculinities, based on long-term ethnographic research in the rural Pacific Northwest of the US; Long Segar, East Kalimantan; and Sitiung, West Sumatra, both in Indonesia. The author concludes by pulling together the various strands of masculine identities and discussing the implications of these various versions of masculinity for forest management. This book will be essential reading for students and scholars of forestry, gender studies and conservation and development, as well as practitioners and NGOs working in these fields.